Integrating AI/ML Workloads with Serverless Cloud Computing: Optimizing Cost and Performance for Dynamic, Event-Driven Applications - Sharmila Ramasundaram Sudharsanam; Gunaseelan Namperumal; Akila Selvaraj (Journal of Science & Technology, 2022)
The convergence of artificial intelligence (AI), machine learning (ML), and serverless cloud computing presents a transformative opportunity for optimizing cost and performance in dynamic, event-driven applications. This paper explores the integration of AI/ML workloads with serverless cloud computing architectures, emphasizing the optimization strategies necessary for managing costs and enhancing performance. With the increasing demand for real-time analytics, personalized services, and intelligent automation in industries such as the Internet of Things (IoT), e-commerce, and financial services, the adoption of serverless computing paradigms for AI/ML workloads has gained traction. Serverless computing offers a distinct advantage by abstracting away infrastructure management, enabling developers to focus on code and application logic while benefiting from automatic scaling, cost-efficiency, and reduced operational complexity. However, deploying AI/ML workloads in serverless environments introduces unique challenges, including managing stateful executions, handling cold starts, optimizing memory and compute resources, and ensuring low-latency responses for real-time applications. This paper provides a comprehensive analysis of these challenges and the associated optimization techniques that can be employed to address them. Key areas of focus include the configuration of memory and CPU resources for serverless functions to balance cost and performance, the use of asynchronous processing models and event-driven architectures to minimize cold start latencies, and the integration of container-based services to manage state and support long-running tasks. The paper also delves into the economic implications of using serverless computing for AI/ML workloads, examining the pricing models of leading cloud service providers and presenting strategies to mitigate costs, such as function composition, data locality optimization, and intelligent workload distribution. Furthermore, this study presents a detailed analysis of several real-world case studies across diverse sectors such as IoT, e-commerce, and real-time analytics to demonstrate the practical applications and benefits of integrating AI/ML workloads with serverless computing. In IoT, for instance, serverless computing enables real-time data processing from millions of connected devices, allowing for scalable, cost-effective analysis and decision-making. Similarly, in e-commerce, serverless architectures can dynamically scale to manage high-traffic events like sales promotions, enhancing customer experience by providing personalized recommendations and reducing latency in transaction processing. Real-time analytics applications benefit from the scalability and flexibility of serverless computing, facilitating rapid data ingestion, transformation, and machine learning model inference for insights on the fly. The integration of AI/ML with serverless cloud computing also aligns with emerging trends in hybrid and multi-cloud deployments, where organizations seek to leverage the strengths of different cloud platforms while optimizing for cost and performance. This paper examines these trends and discusses how serverless computing can be effectively combined with containerized environments and microservices to achieve seamless cross-platform operations and reduce vendor lock-in. The potential for using serverless computing to manage AI/ML pipelines, from data preprocessing and feature engineering to model training and deployment, is explored, with a focus on how this can accelerate the time-to-market for AI solutions while reducing infrastructure costs. Through an exhaustive review of current literature, performance benchmarks, and cost analyses, this paper aims to provide a strategic framework for leveraging serverless cloud computing to optimize AI/ML workloads in dynamic, event-driven applications. It highlights the critical considerations for developers, data scientists, and cloud architects in choosing the right cloud-native tools, services, and design patterns to maximize the benefits of serverless deployments. The discussion concludes by identifying future research directions, including the need for standardized frameworks for AI/ML orchestration in serverless environments, improvements in resource scheduling and provisioning algorithms, and enhanced interoperability between serverless platforms and AI/ML frameworks. By advancing the understanding of how AI/ML workloads can be seamlessly integrated with serverless computing, this paper contributes to the ongoing evolution of cloud-native application development and deployment strategies, fostering innovation and efficiency in a rapidly evolving digital landscape.